Iowa Birdline Update, March 12, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for March 12, 1990. Highlights of the update include sightings of waterfowl, Blackbirds, Bluebirds, Robins, Meadowlarks, and Killdeer being reported from all across the state. Also of note were observations of an Iceland Gull and a Red-necked Grebe. Epson - sheet feed/flatbed